PERHITUNGAN TEMPERATUR KELUARAN DAN MASUKAN PENDINGIN PRIMER DAN SEKUNDER PB-BI DI INTERMEDIATE HEAT EXCHANGER - Epung Saepul Bahrum (Widyariset, 2009)
Analyze of intermediate heat exchanger in Pb-Bi cooled nuclear reactor for hydrogen production design have been done. Based on one dimensional convective and conduction heat transfer model, temperature distribution ofprimary and secondary Pb-Bi at IHX have been modeled. Heat transfer coefficients ofprimary and secondary Pb-Bi coolant are calculated by sub channel analysis method. Primary and secondary Pb-Bi coolant temperature distribution obtained by solving numerically first orders differential equation using Runge-Kutta- Gill method Incase primary coolant flow rate 7000 kg/s and IHX inlet temperature 552°C, outlet temperature and flow rate of Pb-Bi secondary coolant are 542°C and 2700 kg/s. The temperature secondary coolant 542°C corresponds to chemical reaction temperature of steam membrane reforming.